(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This thesis explores the classification of stylistic devices, focusing on lexical stylistic devices, particularly the metaphor. Metaphor, as a figure of speech, holds a central position in linguistic studies due to its pervasive use in both everyday language and literary texts. The paper examines its types, functions, and significance in various communicative contexts.